Penerapan Pengorganisasian Pemberdayaan Masyarakat Pada Posyandu Anggrek 17 - Giranza, Virgian; Siregar, Putra Apriadi; Ramadhani, Tasha Nabila; Sari, Novita; Syahrani, Putri; A.D, Ayu Wulandari; Khofipah, Siti; Novi, Salwa Luthfiyyah; Kholijah, Anna; Ujung, Mariama (Jurnal Abdi Mas Adzkia, 2024)
Posyandu (integrated service post) is the government's effort to provide maternal and child health services to make things easier for the Indonesian people. Posyandu is also an organization that can mobilize local communities to carry out outreach and mutual cooperation to clean the environment around the community so that it can be healthy and clean. The aim of this research is to determine community participation in posyandu, the impact and benefits of posyandu, the obstacles felt by cadres and participants, and also funding to organize the posyandu program. This qualitative research is descriptive. This research collects data by interviewing sources. Interviews were conducted with questions and answers regarding the organization of the Posyandu program with sources who supported this research. Improvements are needed, such as providing more complete facilities, strategic locations, and timeliness of programs, to maintain and increase the effectiveness of community empowerment programs through posyandu. Community participation in empowerment programs, especially through posyandu, has a significant positive impact on monitoring children's health. Community enthusiasm and the active role of cadres in providing education about nutrition, immunization and disease prevention create an environment that supports children's welfare.